Hubungan Indonesia Dengan Brunei Darussalam Melalui Kajian Inskripsi Pada Batu Nisan - Achmad Cholid Shodrie (Berkala Arkeologi, 1994)
Tombstones / graves can be said to be an inscription during the Islamic period because they contain information about who and when someone died. In addition, we can find the lineage of descent and where it came from. Likewise with the findings of inscriptions in Brunei Darussalam cemeteries. Brunei Darussalam's burial sites are in the hills following the path of the river channel Brunei (starting from Luba village a little upstream) to the estuary or vice versa. The relationship that exists between Brunei and Indonesia is not only with Java, because the tombstone inscription mentions several regions in Indonesia. The relationship with the Mataram kingdom in Java is shown in Fatimah's grave in the Diraja cemetery. Besides that, the name of the city (regency) is Magelang. This is shown in the tombstone inscription.